Learning outcomes and qualifications in a changing labour market: the case of teacher education in Greece (Patras) - Georgios Stamelos; Panagiota Evangelakou (Firenze University Press, 2018)
This paper focuses on competences for primary education teachers, which have to be developed during their initial education. Furthermore, we will try to link the discussion on learning outcomes to a comprehensive framework of social needs, central political choices, the strategies of specialized University Departments and students' preferences. To achieve our aim, we will present the results of a research carried out with students in the last year of their initial teacher education at a Greek University (University of Patras). The research used a questionnaire based on competences proposed by Tuning for the scientific field of Education. The results highlight two main points: a) the persistence of tradition and the power of reproduction; b) the difficulty of tuning and harmonizing social needs, political choices, University Department strategy and students' wishes.   Obiettivi formativi e qualifiche in un mercato del lavoro in evoluzione: il caso della formazione per insegnanti in Grecia (Patrasso) Il presente contributo ha per oggetto le competenze richieste agli insegnanti di scuola primaria, da sviluppare nel corso della loro formazione iniziale. L'approccio adottato nell'analisi dei learning outcomes fa riferimento a riflessioni riguardanti bisogni sociali, scelte di natura politica, strategie accademiche a livello dipartimentale, richieste dei soggetti in apprendimento. Il contributo intende presentare i risultati di una ricerca realizzata con studenti dell'ultimo anno del percorso di formazione iniziale all'Università di Patrasso (Grecia). Tale ricerca ha fatto uso di un questionario costruito sulla base delle competenze identificate nella ricerca Tuning (Area Education). I risultati conseguiti hanno messo in luce due aspetti: a) la permanenza della tradizione ed il potere della riproduzione; b) la difficoltà di mettere a punto e armonizzare bisogni sociali, scelte di carattere politico, strategie accademiche gestite a livello di dipartimenti, domande dei soggetti in apprendimento.